The crystal structure of bis(N-oxy-2-(1H-tetrazol-1-yl) acetamide κ2O,O′)-diaqua-zinc(II), C6H12ZnN10O6 - Wang Hui; Xiao Zi-Jing (Zeitschrift für Kristallographie - New Crystal Structures, 2020)
[Zn(C3H4N5O2)2(H2O)2], orthorhombic, Pbcn (no. 60), a = 19.6175(12) Å, b = 7.2887(5) Å, c = 9.3499(6) Å, V = 1336.9(2) Å3, Z = 4, Rgt(F) = 0.0276, wRref(F2) = 0.0605, T = 293(2) K.